Linking Relationship Marketing to Customer Loyalty in The E-Banking Context: The Central Role of Customer Satisfaction - Hoang, Dung Phuong; Nguyen, Nam Hoai (Master in Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2024)
This research examines the interrelationships between relationship marketing, customer satisfaction and customer loyalty in e-banking’s context. The study was conducted in two phases: In-depth interviews and a quantitative survey with a sample of 690 Vietnamese individual and corporate e-banking customers. The research results show that customer satisfaction mediates the impact of relationship marketing on customer loyalty among individual customers. Meanwhile, instead of customer satisfaction, relationship marketing significantly and directly contributes to the loyalty of the corporate customer group. The significance and magnitude of the effects that the five dimensions of relationship marketing’s effectiveness have on customer satisfaction and loyalty, which include the banks’ commitment, customer experience, process-driven approach, service reliability and application of technology, are also different between the two customer segments. This study theoretically contributes to the research stream regarding the mechanism underlying the relationship between relationship marketing’s effectiveness and customer loyalty in the e-banking context, and proposes practical implications for commercial banks to effectively apply relationship marketing in the virtual business environment.